Paradoxes in Scientific Theories and the Boundaries of the Language of Science - Kvasz, Ladislav (Organon F, 2014)
The aim of the paper is to study the analytical and the expressive boundaries of the language of physics. We try to bring these boundaries into a relation with Kant’s theory of antinomies of pure reason. It seems that Kant’s theory can be interpreted as the discovery of the expressive boundaries of the language of science. If this interpretation is tenable, Kant’s discovery is important for the contemporary philosophy of science.
Keywords: Analytical boundaries; antinomies of pure reason; expressive boundaries; Kant